Challenges of mediating investor-state disputes - GOTSIRIDZE, Mariam (Institutional Knowledge at Singapore Management University, 2024)
Mediation has gained a lot of traction in the context of ISDS in the past few years. There are many who truly believe that this could be an alternative to highly costly and lengthy investor-State arbitrations and litigations. States have started to include mediation in their investment treaties; institutions have designed separate mediation rules and procedures specifically for investor-State disputes. The 2022 International Dispute Resolution Survey from the Singapore International Dispute Resolution Academy (SIDRA) is a testament to this positive trend towards investor-State mediation. In the 2022 SIDRA Survey, the respondents signal increased acceptance of mediation in ISDS. Despite these trends, the use of mediation in investor-State disputes appears to be very limited. During the 2022 SIDRA Survey qualitative interviews, the SIDRA tried to enquire about the users’ perspective on the Survey results on mediation and the prospect of the use of mediation for investor-State matters. This article examines the challenges of using mediation in ISDS to propose possible solutions to overcome these challenges. Section II presents the 2022 SIDRA Survey results. Section III outlines and examines user insights collected during qualitative interviews. Section IV proposes possible measures to eliminate the obstacles hindering the use of mediation by States. Section V draws final conclusions.